146 Net protein contribution of feedlots from 2006 to 2017. (5th December 2019) - Baber, Jessica; Sawyer, Jason; Holland, Ben; Karr, Kendall; Word, Alyssa; Wickersham, Tryon
Abstract: Feedlot efficiency has increased as technologies are adopted and new feed ingredients, generally byproducts, have become available and readily incorporated. To evaluate the effect of diet changes and feedlot production over time on net protein contribution (NPC), a deterministic NPC model was used. Lot level production data from 2006 to 2017 for 8 commercial feedlots was used. Ingredient and nutrient composition were collected for a representative starter and finisher diet fed for each year and feedlot combination. Net protein contribution was calculated by multiplying the ratio of human-edible protein (HeP) in beef produced to HeP in feed by the protein quality ratio (PQR). A NPC >1 indicates a production system is positively contributing to meeting human protein requirements, whereas a NPC < 1 indicates competition with humans for HeP. Regressing NPC on year evaluated temporal change in NPC, and feedlots were categorized as increasing (INC; slope > 0) or constant (CON; slope = 0). Four feedlots were categorized as INC and 4 were CON. A common slope was estimated for CON and INC for PQR (P ≥ 0.79). Slopes of INC and CON differed for byproduct and cereal grain inclusion (P ≤ 0.01). Feedlots categorized as INC reduced HeP consumed by 2.39% per year, but CON feedlots did not (0.28%). Cattle received and shipped by INC were lighter than CON cattle (P < 0.01). Both feedlot types tended to improve HeP gained (0.1 kg per year; P = 0.10). Differences in slope for INC and CON were observed for conversion efficiency of HeP (P < 0.01). Net protein contribution increased 0.027 units per year for INC (P < 0.01) and was 0.94 in 2017. Net protein contribution by the feedlot sector increased from 2006 to 2017 as a result of using less human-edible feeds to produce human-edible beef protein.